1964
DOI: 10.2466/pms.1964.18.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Certain Personality Variables to Decision Making in Perception

Abstract: It was hypothesized that certain personality variables would be related to decision making in a guessing experiment. A stimulus set of 100 3- × 5-in. unlined filing cards, 75 of which contained circles and 25 of which were blank, was presented twice to each of 56 undergraduate Ss. The cards were in a random order and Ss were asked to guess whether a circle or a blank would be the forthcoming event. Their predictions on the second session's presentations were quantified in terms of the likelihood of false posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The former finding indicates a weak but significant tendency for persons with high need for approval to be doubtful about their personal efficacy. This relationship has also been reported in a study by Strickland and Rodwan (1963). However, several other studies (Crowne & Liverant, 1963;Seeman, 1963) have reported no relationship between social desirability and control measures.…”
Section: Further Correlates Of the Control Dimensionsupporting
confidence: 80%
“…The former finding indicates a weak but significant tendency for persons with high need for approval to be doubtful about their personal efficacy. This relationship has also been reported in a study by Strickland and Rodwan (1963). However, several other studies (Crowne & Liverant, 1963;Seeman, 1963) have reported no relationship between social desirability and control measures.…”
Section: Further Correlates Of the Control Dimensionsupporting
confidence: 80%
“…Two types of estimates of the observer's criterion for the use of a given response class have been used. Swets, Tanner, and Birdsall (1961) and Strickland and Rodwan (1964) have discussed the use of the ratio of HR to FAR as one such measure. A second type of criterion estimate involves the cumulative standard-score value of HR.…”
Section: Distinction Between the Observer's Sensitivity And Criterionmentioning
confidence: 99%
“…A demonstration of the usefulness of the criterion as a measure of the effects of personality variables in perceptual experiments has been provided by Strickland and Rodwan (1964). Subjects were administered the Marlowe-Crowne Social Desirability Scale as a measure of need for approval.…”
Section: Effects Of Personality and Stimulus Variables On The Observe...mentioning
confidence: 99%
“…Previous work touching on these issues is limited (see, e.g. [ 20 , 21 ])—and we know of no previous paradigm in which subjects had to learn controllability as they performed actions to reach goals.…”
Section: Introductionmentioning
confidence: 99%